Granulomatous-Lymphocytic Interstitial Lung Disease in Common Variable Immunodeficiency—Features of CT and 18F-FDG Positron Emission Tomography/CT in Clinically Progressive Disease - Fraz, Mai Sasaki Aanensen; Moe, Natasha; Revheim, Mona-Elisabeth; Stavrinou, Maria L.; Durheim, Michael T.; Nordøy, Ingvild; Macpherson, Magnhild Eide; Aukrust, Pål; Jørgensen, Silje Fjellgård; Aaløkken, Trond Mogens; Fevang, Børre (Frontiers in Immunology, 2021)
Common variable immunodeficiency (CVID) is characterized not only by recurrent bacterial infections, but also autoimmune and inflammatory complications including interstitial lung disease (ILD), referred to as granulomatous-lymphocytic interstitial lung disease (GLILD). Some patients with GLILD have waxing and waning radiological pathology, but preserved pulmonary function, while others progress to end-stage respiratory failure. We reviewed 32 patients with radiological features of GLILD from our Norwegian cohort of CVID patients, including four patients with monogenic defects. Nineteen had deteriorating lung function over time, and thirteen had stable lung function, as determined by pulmonary function testing of forced vital capacity (FVC) and diffusion capacity of carbon monoxide (DLCO). The overall co-existence of other non-infectious complications was high in our cohort, but the prevalence of these was similar in the two groups. Laboratory findings such as immunoglobulin levels and T- and B-cell subpopulations were also similar in the progressive and stable GLILD patients. Thoracic computer tomography CT scans were systematically evaluated and scored for radiologic features of GLILD in all pulmonary segments. Pathologic features were seen in all pulmonary segments with traction bronchiectasis as the most prominent finding. Patients with progressive disease had significantly higher overall score of pathologic features compared to patients with stable disease, most notably traction bronchiectasis and interlobular septal thickening. 18F-2-fluoro-2-deoxy-D-glucose (18F-FDG) positron emission tomography/CT (PET/CT) was performed in seventeen (eleven with progressive and six with stable clinical disease)17 of the 32 patients and analyzed by quantitative evaluation. Patients with progressive disease had significantly elevated standardized uptake value (SUVmean), metabolic lung volume (MLV) and total lung glycolysis (TLG) as compared to patients with stable disease. Nine patients had received treatment with rituximab for GLILD. There was significant improvement in pathologic features on CT-scans after treatment while there was a variable effect on FVC and DLCO. Conclusion: Patients with progressive GLILD as defined by deteriorating pulmonary function had significantly greater pathology on pulmonary CT and FDG-PET CT scans as compared to patients with stable disease, with traction bronchiectasis and interlobular septal thickening as prominent features.